How is the EUSECON Project Shaping the European Security Research Agenda? - Olaf J. de Groot; Myroslava Purska (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The New Agenda for European Security Economics (EUSECON) is a project that, since 2008, explores the challenges and opportunities in research on human-induced security risks. After defining security as a good that has both public and private characteristics, the research focuses on different elements within the wider issue. The research addresses the factors that influence agents of insecurity and the responses triggered by insecurity threats and security policies. Underpinned by research, the project presents its policy-relevant findings with the goal of improving policy-making in the European Union, disseminating this knowledge to stakeholders, and of promoting information exchange.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330